HUBUNGAN KETERAMPILAN MEMBACA DAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SEMESTER I SD NEGERI LUMUTAN 1 KECAMATAN BOTOLINGGO KABUPATEN BONDOWOSO TAHUN AJARAN 2015/2016 - Syarif Ibnu Rusydi; Nordiana Kholidha (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2015)
This research aims to determine the relationship between reading skills and student’s Indonesian learning outcomes first semester of fifth grade of SD Negeri Lumutan 1 Botolinggo Bondowoso District at academic year 2015/2016. This research is a quantitative non-experimental research with correlation techniques. Hypothesis testing is done by using statistical calculations parametric Spearman Rank correlation techniques. The data correlation coefficient calculation using computer assistance with the program SPSS 17,0 for Windows and the result of correlation coefficient sig. (2-tailed) amount 0,803. This suggests that the presence of a very strong relationship between reading skills and Indonesian learning outcomes of students. After correlation test performed, followed by t-test to test the significance of the relationship. Based on the calculation of the t-test is obtained t count equal to 6,27. For the 5% error level two tail test and dk = n-2 = 22, the obtained t table of 2,074. Provided that if t count > t table then H0 is rejected and Ha accepted. So it can be concluded that the coefficient of correlation between student’s reading skills and Indonesian learning outcomes at 0,803 is significant. Based on testing the hypothesis can be stated that there is a significant relationship between reading skills and student’s Indonesian learning outcomes first semester of fifth grade of SD Negeri Lumutan 1 Botolinggo Bondowoso District of academic year 2015/2016.